Comparison of injury profiles between elite Australian male and female cricket players. Issue 1 (January 2023) - Orchard, John W.; Inge, Philippa; Sims, Kevin; Kountouris, Alex; Saw, Anna E.; Saw, Richard; Beerworth, Kate
Abstract: Objectives: This study presents seven seasons of injury surveillance data for both elite Australian male and female cricket players, revealing injury statistics and allowing for comparison between sexes. Design: Retrospective cohort. Methods: Participants were elite Australian male and female cricket players who were contracted to play for a national and/or state/territory team and/or T20 franchise between 2015–16 and 2021–22 (7 seasons). Injury data was recorded in Cricket Australia's Athlete Management System database and combined with match data. The STROBE-SIIS statement was used as the relevant guideline for this study. Results: Data for 1345 male player seasons and 959 female player seasons revealed sex-related differences in the injury incidence rates and prevalence. Males had higher incidence (average 136 vs 101 injuries per 1000 match days) and prevalence of match time-loss injuries (average 10.4% vs 6.5% players unavailable). However, the overall incidence of all medical attention injuries were similar between sexes (Incidence Rate Ratio (IRR) 0.9, 95%CI 0.8–1.0). The most frequent match time-loss injuries for males were hamstring strains (7.4 new injuries per 100 players per season), side and abdominal strains (5.5), concussion (5.0), lumbar stress fractures (4.3), and wrist and hand fractures (3.9). The most frequent match time-loss injuries for females over the 7 seasons were hamstring strains (3.1), concussion (2.3), quadriceps strains (2.4) and shin/foot/ankle stress fractures (2.0). The IRR of medical attention injuries for males compared to females was higher for lumbosacral stress fractures (IRR 2.3), elbow and forearm injuries (1.5), and concussion (1.4), and lower for lower leg, foot, and ankle stress fractures (0.6), shoulder and upper arm injuries (0.7), and quadriceps strains (0.6). Conclusions: Robust long-term injury surveillance enabled the injury profiles of elite Australian male and female cricket players to be understood and compared. Males had a higher incidence and prevalence of match time-loss injuries, likely reflecting a higher match exposure.